ANALISIS TERJEMAHAN GAYA BAHASA REPETISI DALAM NOVEL A THOUSAND SPLENDID SUNS, TEKNIK DAN KUALITASNYA (KAJIAN PENERJEMAHAN DENGAN PENDEKATAN STILISTIKA) - Murtafi, Anshoffy; Nababan, Nababan; Djatmika, Djatmika (Universitas Sebelas Maret, 2017)
ABSTRACT Anshoffy Murtafi. S131208003. 2016. The Translation Analysis of Repetition Language Style In Novel A Thousand Splendid Suns. The Technicque And Quality (Translation Study Using Stylistics Approach). Supervisors: (1) Prof. Drs. M.R.Nababan, M.Ed, M.A., Ph.D. (2) Prof. Dr. Djatmika, M.A. Thesis. Postgraduated Program In Linguistics Majoring In Translation Studies. Sebelas Maret University. Surakarta. A best-seller novel entitled